Pengembangan Media Audio Visual Mata Pelajaran Biologi Kelas XII IPA SMA Pokok Bahasan Substansi Genetik SMA Negeri 4 Kota Jambi - Deden Darma Wiadi (Jurnal Ilmiah Dikdaya, 2020)
The aim of this reaserch is to get interactive audio visual teaching media on the discussion about teaching Genetic Substance that can be used by teacher and educators so that it can vary and improve teaching and learning quality at senior high school. The method is model designing multimedia based research consisted of five stoges : 1) analysis; 2). Design; 3). Development; 4). Implementation and 5). Evaluation. The outcome of this research was media which were developed very well. It can be describle by the following : (1). Media validity gave good criteria to the media based on the visual look, and (2). Material validity gave good criteria based on the media produced in the research, (3). As a peer evaluation state that the product is worth given to a small Group to learner as a user, (4) student’s response showed from the test given to a small group of student state that this audio visual media had good quality so that it’s easy to understand, (5). Student’s response showed from the test given to a large group of student state that the media produced in this research can improve the student’s interest to study. The research was conducted SMA N 4 Jambi, the subjects were all 12th grade students and the teacher of Biology subject